PENGARUH UBIQUITOUS CONNECTIVITY, PRIVACY CONCERN, DAN INFORMATION OVERLOAD TERHADAP NIAT GENERASI Z UNTUK MENGHENTIKAN PENGGUNAAN PLATFORM TOKOPEDIA DI SURABAYA - Febiola, Febiola; F.C.W. Sutrisno, Timotius; Andrina, Anak Agung Ayu Puty (FEB Universitas Sam Ratulangi Manado, 2024)
The rapid development of digital transformation has significantly impacted the advancement of various shopping platforms, supporting changes in societal lifestyles. This study examines the behavior and motivation of Generation Z in Surabaya regarding online shopping. Factors such as Ubiquitous Connectivity, Privacy Concern, and Information Overload were analyzed to determine their impact on the intention to discontinue using the Tokopedia platform. The research employed a purposive sampling method, gathering respondents from Generation Z in Surabaya and analyzing the data using structural equation modeling. The findings indicate that Ubiquitous Connectivity, Privacy Concern, and Information Overload influence Generation Z's intention to discontinue using the Tokopedia platform in Surabaya. These findings highlight the importance of addressing Ubiquitous Connectivity, Privacy Concern, and Information Overload, as well as discontinuation intentions, for platform providers targeting Generation Z